Analisis Rantai Nilai Industri Ritel Elektronik (Studi Kasus: PT. Electronic City Indonesia Tbk) - Dandi Ramadhan, Muhammad; Valiri Zulfikar , Iqbal; Rufaidah, Popy (IPB University, 2023)
This research aims to produce a map of the industrial value chain at PT. Electronic City Indonesia Tbk uses the industrial value chain analysis model. Researchers use the case study method, an empirical investigation method that examines a recent case or phenomenon in depth and reality, especially when the boundary between wonder and context is unclear. The subject of this research is PT. Electronic City Indonesia Tbk. The results of the research yield information on a list of companies engaged in the Indonesian electronics retail industry, a list of companies as product suppliers for the Indonesian retail sector where they are part of the product manufacturer and assembler industry (PT. Sony Electronics Indonesia, PT. Samsung Electronics Indonesia, PT. Sharp Electronics Indonesia, PT. LG Electronics Indonesia, and others) and a list of companies that are suppliers to the product assembly industry in Indonesia located outside Indonesia (Samsung Electronic, Sharp Corporation, LG Group, and Sony Corporation and others). The value chain of the e-commerce industry conducted by PT Electronic City Indonesia Tbk is relatively simple because it only has links with producers/suppliers and end consumers. There are four actors in the value chain of the retail electronics industry: component or raw material supplier companies, manufacturing companies, retail electronics companies, and end consumers. PT. Electronic City Indonesia Tbk has no products produced under its brand and does not carry out a value-added process. This can be a threat if manufacturers or suppliers experience production problems because it will hinder product sales in the retail electronics industry.